The Masque of the Red Death - Poe, Edgar Allan, 1809-1849 (Salt Lake City, UT : Project Gutenberg, 2010)
"The Masque of the Red Death" by Edgar Allan Poe is a short story first published in 1842. Prince Prospero and a thousand nobles seal themselves inside an abbey to escape a deadly plague called the Red Death. During a lavish masquerade ball in seven color-coded rooms, a mysterious masked figure appears, dressed as a plague victim. As the stranger moves through each chamber, terror spreads among the guests. This Gothic tale explores themes of mortality, isolation, and the futility of escaping death's inevitable reach. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Masque_of_the_Red_Death
Release date is 2010-06-06
Produced by Levent Kurnaz. HTML version by Al Haines.
Keywords: Horror tales, American